ANALISIS FANDOM TERHADAP PERBEDAAN TREATMENT MINGYU DAN WONWOO SEBAGAI BRAND AMBASSADOR ALLO BANK - Chaesya Pricilla Amanda (ADISAM PUBLISHER, 2025)
This study aims to determine how the CARAT fandom perceives and responds to the differences in treatment between Mingyu and Wonwoo as AlloBank brand ambassadors. The method used in this study is a qualitative case study approach with data collection through observation, interviews, and documentation. The results of this study indicate that the differences in treatment between Mingyu and Wonwoo as AlloBank brand ambassadors are perceived as unfair by the CARAT fandom, which affects their trust in AlloBank. Through the S-O-R theory, it was found that the stimulus in the form of unequal AlloBank promotions triggered and emotional acceptance process within fans, resulting in rejection responses such as criticism, boycott activities, and avoidance of the AlloBank. This Study also shows that the fandom’s sensitivity is very high, so the brand needs to consider the values, characteristics, and sensitivity of the fandom as the target in the marketing communication strategy to be implemented